Pengaruh Status Sosial Ekonomi Orang Tua Terhadap Motivasi Belajar Serta Implikasinya Pada Prestasi Belajar Siswa - Hidayat, Ade; Gumilar, Rendra; Kurniawan (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to analyse the effect of parents‘ socioeconomic status (SES) on students’ learning achievement with learning motivation as a mediating variable. This study uses a quantitative approach with the path analysis method on students of class XI IPS SMA Negeri 1 Ciamis. The results showed that parental SES did not have a significant direct effect on learning achievement (β = 0.0322, p = 0.6058), but had an indirect effect through learning motivation which acted as a full mediator (indirect effect = 0.3026, p < 0.001). Learning motivation was shown to have a significant influence on learning achievement (β = 0.5937, p < 0.001). This finding supports Bandura's Social Cognitive Theory and Ryan & Deci's Self-Determination Theory, which emphasise that internal factors are more dominant in academic achievement than external factors. Thus, an increase in SES does not necessarily improve learning achievement in the absence of strong learning motivation.